Guidelines for Community-Based Tourism Development at Ban Nong Phuk Tao Sub-District of Sala Lumduan District, Sakaeo Province - Chantawong, Komol (Rajapark Journal, 2022)
The paper this research to guide the development community-based tourism are applied by participatory action research to define the example of the group of people who inform the main information by purposive sampling are composed of tour guide from community, tour guide from cultural and productionable community, tour guide from the press, members of entrepreneurship in tourism and thirty members of Sala Lumduan Subdistrict Administrative Organization. This research instruments are area survey, interview, checking list and analysis content according to the subject which are discovered can be used inductive descriptive research. Research results describe Guidelines for tourism development include: 1) History and context of the area Community history should be settled in order to develop a legend and story (story). should further develop tourist attractions both conservatively and creatively 3) in terms of the identity of the community Community life should be used to create a meaningful identity. and being a new tourism community 4) Management An integrated participation mechanism should be developed. 5) In terms of income distribution should develop both traditional activities and a variety of community ways to distribute more household income. 6) Facilities Should have developed a public relations website. The tourism map connects both inside and outside the community. and the attributes of being a good host lead to a "Welfare Community for Tourism"